IMPROVEMENT OF THE CLASSICAL COPROOVOSCOPIC FLOTATION METHOD BY USING ASH-FREE FILTERS - Stets, O. V. (Scientific Progress & Innovations, 2019)
Diagnostics is an important stage in the process of treatment and ensuring epizootic well-being. The faster and more accurate the diagnosis, the higher is the level of providing treatment-preventive measures. At present, many methods of diagnosing infectious and non-infectious diseases have been developed in the world. A considerable number of these methods are connected with studying invasion diseases of productive animals. Now, quite a few methods as to diagnosing parasitic diseases of reptiles with low body weight are described in literature. That is why developing effective and convenient methods of diagnosing parasitic diseases of the indicated species of animals with low body weight are an urgent problem requiring solution. In connection with the above-mentioned, the aim of our research was to improve the classical Fulleborn flotation method for the needs of laboratories in the study of reptiles. The investigations were conducted during 2016–2018 in the laboratory of the Department of Parasitology and Tropical Veterinary Medicine of the National University of Life and Environmental Sciences of Ukraine. For coprological study, feces samples were taken of panther chameleons (Furcifer pardalis Cuvier, 1829). After conducting the experimental part of the work, it was revealed that the improved flotation method using ashless filters was 10 % more effective than the analog method in terms of quality index (the number of positive samples). Studying quality indices of the coproovoscopic diagnostic method effectiveness, it was found that it was highly effective in detecting oxyuris eggs, since it enabled to detect 59.1 % more nematode eggs in comparison with the prototype method (2.2±4.5 egg specimens as compared with 0.9±1.9). The effectiveness index was slightly lower while detecting nematodes of the species Spinicauda freitasi. It was found that the proposed method enabled us to identify 54.9 % more eggs as compared with the classical method (18.4±32.4 egg specimens versus 8.3±15.4 specimens). Also, this technique was 35.9 % more effective in detecting pathogen eggs of Hexametra angustiaecoides than the classical method. Thus, the improved method enables to identify a number of pathogens of nematodoses in panther chameleons, despite insignificany amount of the studied material.